Ejector based CO2 transcritical combined cooling and power system utilizing waste heat recovery: A thermoeconomic assessment. (15th April 2019) - Ipakchi, O.; Mosaffa, A.H.; Garousi Farshi, L.
Highlights: A novel transcritical CO2 ejector based combined cooling and power system is introduced. A thermoeconomical model is developed to evaluate the enhanced proposed system. A multi-objective optimization is carried out to find the optimum operating condition. Unlike old proposed systems, the net power output of this system is positive. Abstract: To reduce the fossil fuels consumption and their environmental impact, improve the waste heat efficiency, an enhanced transcritical CO2 ejector based combined cooling and power system is proposed using recovered waste heat. This system can employ in vehicles and make them run more environmentally friendly. The new proposed system includes a power generation part and a transcritical ejector based refrigeration system. A thermodynamical model is developed to evaluate the enhanced proposed system. A comprehensive parametric investigation and thermoeconomic analysis are presented to study the effects of key parameters on the thermoeconomic performance of the system. The results show that back pressure of ejector (gas cooler pressure) plays the main role to improve the system performance. A 10 bar increase in ejector back-pressure of ejector leads to an increase of 16.4% in energy efficiency while the exergy efficiency decreases of 9.2%. From exergy analysis, it is found that the biggest irreversibility in the system belongs to the internal heat exchanger used between pump and turbine outflows. For the cooling capacity of 10 kW, a multi-objective optimization is carried out and the optimal values of energy and exergy efficiencies obtained from the Pareto frontier results are 27.42% and 24.21%, respectively, while it leads to the net power output of 7.55 kW. In this case, the net present value and the simple payback period of the proposed system are equal to 0.3419 M$ and about 4 years and 6 months, respectively.